Tryptophan metabolism and immune regulation in the human placenta. (September 2021) - Silvano, Angela; Seravalli, Viola; Strambi, Noemi; Cecchi, Marta; Tartarotti, Enrico; Parenti, Astrid; Di Tommaso, Mariarosaria
Highlights: Pregnancy is a complex process, with a semi-allogeneic fetus that requires immune privilege and surveillance from pathogens. An active immunological tolerance in pregnancy is insured by pro-tolerogenic hormones, cytokines, immunomodulatory molecules, T cells and other cell types involved in immune response. Tryptophan catabolized by indoleamine 2, 3-dioxygenase and tryptophan 2, 3- dioxygenase in Kynurenine pathway is involved in immunoregulation. Knowing the immune mechanisms involved in the active tolerance towards an allogeneic fetus can clarify the pathogenesis events in pregnancy. Abstract: The placenta represents the maternal-fetal vascular interface. It is capable of supplying the bioenergetic needs of the developing conceptus. It is composed of different cell types that engage in highly varied functions, ranging from attachment, invasion and vascular remodeling to cell fusion, hormone production, and nutrient transport. A deep knowledge of the immunological mechanisms responsible for maintaining an active tolerance towards an allogeneic fetus and the anti-inflammatory properties of the placenta can be useful to clarify the pathogenesis of adverse events in pregnancy. While the systemic mechanisms of this immunological regulation in pregnancy have been well studied, the metabolic processes involved in the placental immune response are still poorly understood. The aim of this review is to summarize the most important information concerning the immune regulation in pregnancy, focusing on the role of tryptophan (Trp) catabolism performed by indoleamine 2, 3-dioxygenase (IDO) and tryptophan 2, 3-dioxygenase (TDO) in the placenta.